Control of bacteriochlorophyll accumulation by light in Rhodobacter capsulatus. - Biel, A J (1986)
The accumulation of bacteriochlorophyll in Rhodobacter capsulatus grown either anaerobically or under low aeration is repressed by bright light. It has been proposed that an intact photosynthetic membrane system is required for light-mediated regulation. This was tested by measuring bacteriochlorophyll accumulation in various mutant strains grown under 3% oxygen. Mutants lacking either the reaction center and B875 complexes or the B800-850 complex exhibited normal regulation of bacteriochlorophyll accumulation by light, suggesting that neither photosynthesis nor the photosynthetic membrane system is involved in light-mediated regulation. Bright light did not reduce transcription from the bchA, bchC, bchE, or bchF gene. Neither a bch+ strain nor bchG or bchH mutants accumulated greater than normal amounts of any bacteriochlorophyll precursor when grown in bright light, indicating that carbon flow over the bacteriochlorophyll biosynthetic pathway was not being regulated by light intensity. When exposed to bright light, R. capsulatus converted aminolevulinate into a colorless compound with Rf values very similar to those of bacteriochlorophyll. These results suggest that in strains grown under low aeration, light intensity controls bacteriochlorophyll accumulation, but does not control bacteriochlorophyll synthesis.